A ANALISIS FAKTOR DOMINAN YANG MEMPENGARUHI PERILAKU KLIEN HIPERTENSI DALAM UPAYA PENCEGAHAN KEKAMBUHAN DI DESA PACING WILAYAH KERJA PKM BANGSAL MOJOKERTO - Ibnu, Faisal; Khaidhir, Khaidhir; Mustadi, Mustadi (Jurnal EDUNursing, 2024)
Hypertension is a disease that is most commonly experienced by people and usually appears without any complaints, so many clients do not know that they suffer from hypertension. Until now, hypertension is still a major problem and is the first cause of death in the world. This study aims to determine the dominant factors that influence the behavior of hypertensive clients in efforts to prevent recurrence in Pacing Village, Bangsal Mojokerto health center working area. The research design uses correlational analytics with a cros sectional approach. The number of samples in this study was 84 respondents from 125 hypertensive clients in the Bangsal Mojokerto health center working area. The data collection instrument used in this research was a questionnaire. Based on the results of statistical tests, it shows that the factors that influence hypertension prevention behavior include: age factor with a p value of 0.000, gender with a p value of 0.000, occupation with a p value of 0.000, level of education with a p value of 0.000, history of hypertension with a p value of 0.049 , marital status p value 0.031, physical activity p value 0.000, smoking habit p value 0.046, coffee drinking habit p value 0.001 and obesity p value 0.000. The dominant factor influencing the prevention behavior of clients with hypertension is the work factor with a p value of 0.000 and a Pearson value of 43.321. Hypertensiion clients must pay attention to various factors that can be changed, including: physical activity, coffee drinking habits and obesity to increase efforts to prevent hypertension. Keywords: Dominant factors, preventive behavior, hypertension